Perlindungan Hukum Terhadap Pekerja/Buruh dalam Perjanjian Kerja Waktu Tertentu yang Mengandung Klausula Baku Studi Kasus Pada Perusahaan Wedding & Event Organizer - Istianah (Faculty of Law, Universitas Airlangga, 2024)
This thesis discusses the validity and legal consequences of work agreements for a set period of time (PKWT) that include standard clauses, using case studies from Wedding & Event Organizer companies. PKWT that include standart clauses is valid as long as it meets the legal requirements of the agreement in Article 1320 BW (1) and there is no abuse of circumstances in making an agreement by the parties, so it is important for the government to issue decisions that can be used as a legal basis for the use of standard clauses in making PKWT. The consequence of being violated of Article 1320 BW (1) is the agreement can be calcelled. So, it is important to formed a special institution to oversee the actions of employers in make terms of doing work relations as not to harm the workers/labourers more